A study on ESL learners' reading preferences between printed text and onscreen text - Jamil, Hafizan Kono (2013)
Since the growth of information technology, books do not hold the exclusive rights as the only knowledge contributor. Readers have more choices of materials for reading activity since reading text is now available in digital format. In order to ensure readers’ will select the most effective reading materials, teacher has to be aware of the benefits and drawback of reading onscreen and in print. Thus, this research is done to identify factors influencing readers’ choice between reading onscreen and in print. This research will also investigate the readers’ preference between reading onscreen and in print. In addition, respondents in this study were also asked on possible problems encountered when reading either of the formats mentioned above. The research was carried out on 30 post-graduate TESL students from UTM Skudai. Data for this research was collected from questionnaire and interview. The research findings indicated that regardless of the technology advancement, in print reading seems to be in favour among the language practitioner. Readers also indicated that engagement towards content in the text is the most influential factor determining their choice of reading format. This research is hoped to be used in improving teachers’ understanding of current language learners reading trend. It is also can be used as a basis for improvement in teachers’ training syllabus in identifying the most effective format for L2 reading comprehension.